2012
DOI: 10.3109/0886022x.2012.691012
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in 5/6 Nephrectomized Rat Model: Effect of Alpha-Lipoic Acid

Abstract: Alpha-lipoic acid (ALA) is a powerful antioxidant, and its effect in ameliorating complications of diabetes mellitus has been widely documented. The aim of this study was to investigate the role of ALA in the disease progression of remnant kidneys (RK). Systolic blood pressure (SBp), hemoglobin, renal function, kidney malondialdehyde (MDA), glutathione (GSH), vitamin E (Vit E) concentrations, p65 nuclear factor (NF)-κB activity, and macrophage infiltration were analyzed in sham and RK rats supplemented with AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…High oxidative stress levels, as indicated by plasma MDA concentration, was found to be significantly higher in Nx animals [3133]. This finding is in agreement with our observation in nephrectomized rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…High oxidative stress levels, as indicated by plasma MDA concentration, was found to be significantly higher in Nx animals [3133]. This finding is in agreement with our observation in nephrectomized rats.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies reported a beneficial effect of antioxidant treatment on MDA concentration or ROS in CKD. One of these studies showed that alpha-lipoic acid, an antioxidant, attenuated kidney MDA concentration in Nx rats [33]. Another study reported that sildenafil-treated Nx rats had decreased ROS levels [34].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, beneficial effects of LA in the 5/6 nephrectomy model in rats have been observed with intraperitoneal injections of LA. 13 However, it has been reported that the oral administration presents the highest LD50 in rats and mice, when compared with other routes of application.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies showed that oral administration of LA, particularly to hemodialysis (HD) patients for several weeks, led to an improvement in asymmetric dimethylarginine (ADMA) 7 and C-reactive protein 8 levels, or erythropoietin resistance index, 9 oxidative stress biomarkers levels were not altered in the LA-treated groups of CKD 10 or HD patients. 8,9,11,12 In experimental CKD, intraperitoneally-injected LA for 8 weeks has been shown to improve blood pressure, renal function, and oxidative markers after 5/6 nephrectomy in rats, 13 while oral LA for 8 weeks decreased blood pressure, as well as vascular injury 14 when compared with the non-treated nephrectomized rats. In acetaminophen-induced uremia, orally-fed LA for 15 days prevented an increase in plasma urea, creatinine, and malondialdehyde levels in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation